Development of an E-Learning Platform For EMTs In Ghana. Issue Volume 34:Issue s1(2019) (May 2019) - Bonney, Joseph; Namburete, Ana I. L.; Dagadu, Sesinam; Quao, Nana Serwaa; Osei-Ampofo, Maxwell; Awariyah, Dominic; Cobbold, Sonia
Abstract : Introduction: The continuous development of the knowledge and skill of the emergency medical technicians (EMTs) in Ghana is important for the success of the pre-hospital system. Due to distance and time constraints, an online e-learning platform is a good way to educate the Emergency Medicine Technicians in Ghana. Aim: The study looked at the feasibility of developing a distant learning module for the training and continuous medical education of EMTs. Methods: EMTs in the Ashanti Region were randomly selected to be part of the study. They received online lectures and notes that were accessible by their mobile phones. They all received a test at the end of each model. The study measured their willingness to participate, average attendance for each model, and the scores for each model test. The study also measured the overall feasibility of the distant learning program. Results: The study developed a training course comprised of 7 modules: trauma and surgical emergencies, obstetric emergencies, pediatric emergencies, disaster management, medical emergencies, basic ultrasound, and medical research. Tests and quizzes were electronically sent to EMTs over the course of the research period, with an average test score of 70.14% (low: 35%, high: 95%) for the cohort. Feedback from participants showed gains in knowledge and skill delivery. The average attendance for all model was 56.6% ranging from 47.37%-63.16% for the models. Challenges for attendance included internet access, heavy duties, and other personal reasons. The post-training interview showed 100% willingness to participate in future online programs with the most common reasons stated as low cost, ease of attendance for models, and reduced expense. Discussion: The study concluded that online, distant learning models can be used in Ghana for training and continuous medical education for EMTs. It is an easy and cost-effective model compared to a face-to-face model.